Analysis of Factors Influencing the Financial Behavior of Gen Z during the Covid-19 Pandemic - Ratri Paramitalaksmi; Wuku Astuti; Hadjija Dewi Aviva (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to find out factors influencing financial behavior of Gen Z during the Covid-19 pandemic in Yogyakarta, Indonesia. The method used in this study was by distributing questionnaires to 200 students in Yogyakarta who was born in the years after 1995 to 2010 by sampling method through Google Form. This sampling determination is expected to be a representative of Gen Z in Yogyakarta, Indonesia. The result of this study is that he lower level of financial literacy the higher the Gen Z’s financial behavior, the higher lifestyle the higher the Gen Z’s financial behavior and girls of Gen Z has higher financial behavior than bos of Gen Z during the Covid-19 Pandemic in Yogyakarta, Indonesia.